The impact of real-time ultrasound guidance on ventricular catheter placement in cerebrospinal fluid shunts – a single-center study - Sarikaya-Seiwert, Sevgi; Schievelkamp, Arndt-Hendrik; Born, Mark; Wispel, Christian; Haberl, Hannes; Shabo, Ehab (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Misplacement of ventricular catheters during shunt surgery occurs in 40% of cases using a freehand technique and therefore represents a risk for early shunt failure. The goal of this retrospective, single-center study is to analyze the impact of real-time ultrasound guidance on ventricular catheter positioning and early outcome of shunt survival.We analyzed the charts and images of all patients who underwent shunt surgery from 09/2017 to 12/2022 and compared the position of the ventricular catheter using the freehand technique and real-time ultrasound guidance. Central catheter position was graded as grade I (optimal), II (contact with ventricle structures or contralateral), and III (misplacement).A ventricular catheter was placed in 244 patients using real-time US guidance and in 506 patients using a freehand technique. The mean age (53.4 and 53.6 years, respectively) and the preoperative frontal occipital horn ratio (FOHR; 0.47 versus 0.44) were almost equal in both groups. In the study group, grade I catheter position was achieved in 64% of cases, grade II in 34%, and grade III in 2%. The control group showed grade I position in 45%, grade II in 32%, and grade III in 23% of cases (p<0.05). An early central catheter failure rate was the highest in grade III (40.5%) compared to 4% in grade I.Our data demonstrate that real-time US guidance leads to a significant improvement in ventricular catheter placement. Consequently, early shunt revisions decrease significantly. Further prospective, randomized, and controlled studies comparing the standard method to real-time ultrasound catheter placement are required.
Keywords: shunt; US-guided; ventricular catheter